ETNO-ETIK TANEAN LANJHENG: KONSTRUKSI ETOS BISNIS KELUARGA MUSLIM MADURA - Firman Setiawan; Sirajul Arifin (LP2M Universitas Ibrahimy, 2020)
The Madurese are one of the ethnic groups in Indonesia who have a unique character, namely religious, hard-tempered, firm, brave, upholding self-esteem, and have high solidarity and brotherhood. From these characters then emerged and known one character that is quite amazing from the ethnic Madurese, which has a high work ethic. This can be seen for example from their perseverance in fighting for their socio-economic life. Even when Madura's natural conditions do not allow exploitation to improve their economic lives, migrating is one of the paths taken. Their strong work ethic can be genetically acquired, but it is also very likely to be influenced by the religion and socio-culture that develops in their environment. Especially for those who live in families who live in an environment known as tanean lanjhang. Growing culture and very close family ties in this environment have resulted in the transfer of religious values ​​and work ethics from parents to their juniors to be very effective. The characteristics and work ethics of Madurese, especially those who live and live in the Tanean Lanjhang environment, are ambitious and hard-working, have high solidarity, are responsible and work-oriented. If seen from the religious understanding adopted and believed by the Madurese people, that human actions have something to do with the provisions of God, but God gives the human potential to try and endeavor. This is what then makes Madurese so persistent in fighting for their socio-economic life even though natural conditions do not allow exploitation and maximum utilization. This understanding is inseparable from the teachings that are so deeply rooted in Muslim circles of Madura, they are Ahlu Sunnah Waljama'ah al-Nahdliyah.